Antidepressant response to aripiprazole augmentation associated with enhanced FDOPA utilization in striatum: a preliminary PET study - Conway, Charles R.; Chibnall, John T.; Cumming, Paul; Mintun, Mark A.; Gebara, Marie Anne I.; Perantie, Dana C.; Price, Joseph L.; Cornell, Martha E.; Mcconathy, Jonathan E.; Gangwani, Sunil; Sheline, Yvette I. (Psychiatry Research, 2014)
Several double blind, prospective trials have demonstrated an antidepressant augmentation efficacy of aripiprazole in depressed patients unresponsive to standard antidepressant therapy. Although aripiprazole is now widely used for this indication, and much is known about its receptor-binding properties, the mechanism of its antidepressant augmentation remains ill-defined. In vivo animal studies and in vitro human studies using cloned dopamine dopamine D2 receptors suggest aripiprazole is a partial dopamine agonist; in this preliminary neuroimaging trial, we hypothesized that aripiprazole's antidepressant augmentation efficacy arises from dopamine partial agonist activity. To test this, we assessed the effects of aripiprazole augmentation on the cerebral utilization of 6-[(18)F]-fluoro-3,4-dihydroxy-l-phenylalanine (FDOPA) using positron emission tomography (PET). Fourteen depressed patients, who had failed 8 weeks of antidepressant therapy with selective serotonin reuptake inhibitors, underwent FDOPA PET scans before and after aripiprazole augmentation; 11 responded to augmentation. Whole brain, voxel-wise comparisons of pre- and post-aripiprazole scans revealed increased FDOPA trapping in the right medial caudate of augmentation responders. An exploratory analysis of depressive symptoms revealed that responders experienced large improvements only in putatively dopaminergic symptoms of lassitude and inability to feel. These preliminary findings suggest that augmentation of antidepressant response by aripiprazole may be associated with potentiation of dopaminergic activity.
EVALuna2:13842